Effect of intestinal resection on human small bowel motility. Issue 6 (June 1996) - Schmidt, T; Pfeiffer, A; Hackelsberger, N; Widmer, R; Meisel, C; Kaess, H
Abstract : BACKGROUND: Few data are available on adaptive changes of human small bowel motility after intestinal resection. AIM: To characterise jejunal motility after extensive and limited distal intestinal resection. METHODS: Seven patients with a short bowel syndrome after total ileal and partial jejunal resection (residual jejunal segments between 60 and 100 cm) and six patients with limited distal ileal resection (resected segment between 30 and 70 cm) underwent ambulatory 24 hour jejunal manometry 15 (6-24) months after the operation. Normal values were obtained from 50 healthy subjects. Fasting motility and the motor response to a 600 kcal solid meal were analysed visually and by a computer program. RESULTS: Limited ileal resection did not result in changed jejunal motility. After extensive distal resection, patients had a significantly shorter migrating motor complex (MMC) cycle and a significantly shorter duration of the postprandial motor response compared with controls (p < 0.005). Intestinal resection had no influence on jejunal contraction frequency and amplitude and did not lead to any abnormal motor pattern. CONCLUSION: Extensive distal resection of the small intestine produces distinct abnormalities of fasting and postprandial motility in the intestinal remnant. The shortening of digestive motility and the increased frequency of MMC cycling could contribute to malabsorption and diarrhoea in the short bowel syndrome.